The construction of the flow duration curve and the regionalization parameters analysis in the northwest of China - Jinkai Luan (IWA Publishing, 2021)
Daily runoff is the data to estimate the water resources in a river. In many catchments, the daily discharge is not well observed. Flow duration curve is an important characteristic of daily runoff, and important for the design of water conservancy projects. In the ungauged catchments, the evaluation of distribution functions and the parameters of flow duration curve is a helpful method to understand the characteristics of the flow. This study uses data from 19 hydrological stations to evaluate the applicability of 11 distribution functions to simulate flow duration curves in the northwest of China. The fitted flow duration curves are evaluated by Nash-Sutcliffe efficiency, the root mean square relative error and the coefficient of determination. The evaluation shows that, among the 11 distribution functions, the log normal model is the most suitable model to construct flow duration curves of 19 hydrological stations. Based on a multivariate linear regression model, a regional model of distribution parameters is constructed, including functions of watershed geomorphologic and climatic characteristics. The analysis of Baijiachuan hydrological station shows that the parameters a and b showed a decreasing trend. This study presents an innovative approach to evaluate regionalized parameters of flow duration curves considering the impacts of geomorphologic and climatic characteristics. HIGHLIGHTS Daily discharge at 19 hydrological stations in the northwest of China are used to evaluate the applicability of 11 distribution functions to simulate flow duration curves.; The log normal distribution function is the most suitable model to construct flow duration curves.; A regional model of distribution parameters is constructed, and they are functions of watershed geomorphologic and climatic characteristics.;